Gambaran tingkat wellness pada mahasiswa Prorgam Studi Pendidikan Dokter Fakultas Kedokteran Universitas Udayana angkatan 2015 - 2017 - Kevin Kusuman; I Putu Adiartha Griadhi; I Made Krisna Dinata (Intisari Sains Medis, 2020)
Background: Medical students, as academic people, in the course of his lectures can not be separated from various stresses. Causes of stress can be sourced from academic life, such as demands from lectures, examinations held every two weeks, and OSCE examination at the end of each semester. These demands also include changes in competence and the increasing complexity of lecture materials that increasingly difficult.Aim: This study aims to know the level of the wellness of medical students, so that if there is a lack of dimension, the results can be used as self – reflection to be a better person.Methods: A descriptive observational study with cross-sectional study design was conducted in January 2018. Wellness was measured through seven dimensions, namely emotional, enviromental, intellectual, occupational, physical, social, and spiritual. Respondents in this study were active students as many as 143 students from the number of affordable population of 740 students using stratified random sampling.Results: From 143 study samples, 43 people were male (30.1%) and 100 people were female (69.9%). 141 people had good environmental and social wellness. Meanwhile, 35 people had low physical wellness.Conclusion: The results showed that the wellness dimension of the highest number of categories was enviromental and social wellness (98.6%), then intellectual wellness (96.5%), spiritual wellness (95.1%), occupational wellness (86.7%), emotional wellness (76.9%), and the lowest is physical wellness (75.5%). Latar belakang: Seorang mahasiswa kedokteran dalam proses perkuliahannya tidak terlepas dari berbagai stres. Penyebab stres dapat bersumber dari kehidupan akademiknya, seperti tuntutan dari tugas kuliah, ujian yang dilaksanakan setiap dua minggu sekali, dan ujian OSCE di setiap akhir semester. Tuntutan ini juga termasuk perubahan kompetensi dan meningkatnya kompleksitas materi perkuliahan yang semakin lama semakin sulit. Tujuan: Tujuan dari penelitian ini adalah untuk mengetahui gambaran tingkat wellness mahasiswa kedokteran, sehingga jika nantinya terdapat dimensi yang kurang, hasil tersebut dapat digunakan sebagai refleksi diri untuk menjadi yang lebih baik.Metode: Penelitian ini menggunakan rancangan penelitian deskriptif potong lintang dan dilakukan pada bulan Januari 2018. Wellness diukur melalui tujuh dimensi, yaitu emotional, enviromental, intellectual, occupational, physical, social, dan spiritual. Responden dalam penelitian ini adalah mahasiswa aktif sebanyak 143 mahasiswa dari jumlah populasi terjangkau 740 mahasiswa dengan menggunakan stratified random sampling. Hasil: Dari 143 sampel penelitian yang termasuk dalam jenis kelamin laki laki sebanyak 43 orang (30,1%) sedangkan untuk jenis kelamin perempuan sebanyak 100 orang (69,9%). 141 orang memiliki environmental dan social wellness baik Sementara 35 orang memiliki physical wellness yang kurang.Kesimpulan: Dari penelitian ini bisa disimpulkan bahwa dimensi wellness dari jumlah kategori baik yang tertinggi adalah enviromental dan social wellness (98,6%), selanjutnya intellectual wellness (96,5%), spiritual wellness (95,1%), occupational wellness (86,7%), emotional wellness (76,9%), dan yang terendah yaitu physical wellness (75,5%).